Validation of the PsAID-12 Russian questionnaire in patients with psoriatic arthritis - L. D. Vorobyeva; E. Yu. Loginova; Yu. L. Korsakova; E. E. Gubar; P. O. Tremaskina; T. V. Korotaeva (Научно-практическая ревматология, 2022)
Objective – validation of the Russian-language version of the PsAID-12 questionnaire in patients with psoriatic arthritisMaterials and methods. The study included 187 patients, mostly men (50.2%), with a reliable diagnosis of psoriatic arthritis (PsA) according to the CASPAR criteria (2006), who consistently sought medical help at the V.A. Nasonova Research Institute of Rheumatology and those who signed informed consent to participate in the study. Average age was 45.6±11.7 years, duration of PsA – 113.8±76.7 months, duration of psoriasis – 241±144 months, disease activity according to DAPSA (Disease Activity in Psoriatic Arthritis) – 29.1±22.6. At the initial visit and after 12 months of therapy, all patients underwent a standard rheumatologic examination and assessment of the quality of life. The number of tender joint count (TJC 68), the number of swollen joint count (SJC 66), PGA (patient global assessments) were assessed using a visual analogue scale (VAS) (0–10 cm), VAS pain (0–10 cm), BASDAI (Bath Ankylosing Spondylitis Disease Activity Index), PsAID-12 (Psoriatic Arthritis Impact of Disease-12) and EQ-5D (EuroQoL-5D). The EQ-5D was considered the “gold standard” for assessing quality of life. The reliability of the PsAID-12 questionnaire was studied on the basis of its reproducibility by test-retest analysis and internal constancy by calculating the Cronbach’s alpha for each scale. We assessed the validity, i. e., the ability of the PsAID-12 questionnaire to reliably measure its characteristics based on criterional and constructive validity. The criterion validity was calculated by assessing the relationship between PsAID-12 and “external criteria”| reflecting the activity of PsA and interchangeability with the EQ-5D questionnaire using correlation analysis. A moderate and strong bond was considered r≥0.30. Constructive validity was assessed by the method of “known groups” and factor analysis. The study of the reliability of the PsAID-12 questionnaire was carried out in 30 PsA patients. Sensitivity – in 172 patients in dynamics after 12 months of various PsA therapy regimens.Results. The study of the reliability of the PsAID-12 questionnaire included 30 patients. According to the results of the test-retest analysis, it was revealed that there were no statistically significant differences between the initial and repeated assessments on all 12 PsAID-12 scales (p>0.05). To assess the internal constancy, the Cronbach’s alpha was calculated for each of the 12 scales of the questionnaire. The value of this coefficient ranged from 0.8 to 0.9 and was quite high. Validity was assessed in 187 patients with PsA. The analysis of the criterion validity of the PsAID-12 questionnaire was studied by assessing the relationship of its scales with the scales of the EQ-5D questionnaire, where it demonstrated a close correlation (r>0.3). That testifies to the good interchangeability of this questionnaire. Also, the criterion validity was carried out by assessing the “external criteria” (TJC 68, SJC 66, DAPSA, VAS global assessments, VAS global pain, BASDAI). Where were identified direct correlations of external criteria with all scales of the questionnaire. The highest correlation coefficient (r=0.8) was found between the BASDAI index and the “Physical performance” scale. When assessing constructive validity by the “known groups” method, patients were divided into 2 groups according to disease activity: with DAPSA index ≥5 and DAPSA index ≤4. Significant differences were revealed between the group of patients with active PsA and the absence of PsA activity on all scales of the questionnaire (p<0.001). Factor analysis revealed two main factors – physical and emotional health; a high level of correlation of the scales with their factor was also shown. To assess the sensitivity of the questionnaire, its changes were analyzed depending on the achieved effect on therapy after 12 months: group I of patients in whom MDA was achieved – 50 patients; group II – 43 patients REM/LDA; group III – 79 patients with no effect on therapy. It was revealed that in groups I and II there was a statistically significant difference on all scales of questionnaires, in group III, “non-responders” to therapy, there were no statistically significant improvements in the scales “Pain” (p=0.37), “Fatigue” (p=0.15), “Skin problems” (p=0.23), “Work and/or leisure activities” (p=0.056), “Functional capacity” (p=0.44). Thus, during treatment, it was noted that the PsAID-12 questionnaire may reflect the dynamics depending on the activity of the disease during treatment, which proves its good sensitivity.Conclusion. The Russian version of the PsAID-12 has good psychometric properties and is able to reflect changes in the patient’s health status over time, along with disease activity and laboratory manifestations.